THE SOURCES OF WRITING BUSTAN AL-SALATIN BY NUR AL-DIN AL-RANIRI: A STUDY BASED ON BOOK I-BOOK IV - Hamzah, Norhayati Hj (Journal of Al-Tamaddun, 2020)
Bustan al-Salatin fi Dhikr al-Awwalin wa al-Akhirin (The Garden of the Kings on the Recollection of the Past and Present) (henceforth Bustan) is a masterpiece of Islamic history written by Nur al-Din al-Raniri (cited hereafter al-Raniri) in the seventeenth century Aceh. It is the best-known work of al-Raniri on history and the biggest book written in the history of traditional Malay literature that consists of seven books with the total of 60 chapters. The large contents of Bustan comprise of universal history and a “mirror for rulers” covers the period from the creations of the world until the Malacca and Aceh Sultanates in the Malay World. Accordingly, numerous and different kinds of sources and references were used by al-Raniri in writing Bustan. Therefore, this article endeavours to analyze the sources in Book I-Book IV of Bustan. This research is a qualitative research that applies the technique of documentation in collecting data while inductive approach to content analysis was utilized for data analyzing. The main documents used were the two versions of the manuscript of Bustan (Raffles Malay 8 and UM 41). The finding indicates that al-Raniri used distinct types of authentic sources of Islamic history especially the Qur’an and hadith which is evident in the utilization of 167 Qur’anic verses and 216 hadith. Qur’anic verses were mainly used in the narration on the creation of the universe, while hadith communicated the stories of the caliphs and former kings’ conduct.